Strength Analysis in Bonded, Bolted and Bolted-Bonded Joints, Single Lap Joints, Metal/Composite Plates - Ali Sadık; Filiz Karabudak (Applied Sciences, 2023)
Today, especially in many fields that require structural durability, such as the aerospace and automotive industries, there has been a need to use different bonding techniques separately or together in order to use materials together with different mechanical properties. In this study, stress and damage analysis of single lap joints, bonding and bolt-bonding metal/composite joints under tensile loads were performed. The nine kinds of single lap joint models in different combinations (bonded, bolted and bolt-bonded) were prepared by using acrylic adhesive (Acrytron 1E1) and 100-25-3 mm in size; AZ91/AZ91, AZ91-carbon fiber and carbon fiber-carbon fiber plates. Some comparisons were carried out by examining the stresses and deformations that occur in joint models exposed to tensile and 4-point bending tests. As a result of the tensile test, it was determined that the highest maximum tensile stress occurred in AZ91-CF bolt-bonded samples. In the four-point bending test, the maximum shear force value was determined in the CF-CF bolted-bonded samples.